Factors Influencing Senior Practicum Readiness for Nursing Practice: A Descriptive Correlational Study. - Nease, Beth; Corbett, Cynthia F.; Armstrong, Stephanie; Wang, Kesheng; Casey, Kathy; Chen, Kong (Journal of Nursing Education, 2026)
Background: This study investigated the influence of belongingness, self-efficacy, and clinical learning support on readiness for nursing practice and explored the role of demographic factors and nursing program differences. Method: A quantitative, descriptive approach was used to explore undergraduate prelicensure senior nursing students' perceptions across the United States. Results: Descriptive statistics, Pearson correlation, and multiple linear regression demonstrated students in traditional Bachelor of Science in Nursing programs reported significantly higher scores across all domains compared with those in associate degree programs (p <.01). Similarly, students in programs with ≤400 clinical hours and those assigned only one preceptor scored significantly higher on all measures (p <.01 and p <.05, respectively). Regression analysis indicated self-efficacy and learning support explained 47.9% of the variance in practice readiness (p <.05). Conclusion: These findings share how clinical experiences shape students' readiness for nursing practice. Recommendations include optimizing clinical hour requirements, limiting preceptor variation, and enhancing support systems.